Delivering the 'D' in Transit-Oriented Development: Examining the Town Planning challenge - Curtis, Carey (University of Minnesota, Department of Civil Engineering, 2012)
This paper examines the extent to which different town planning approaches succeed in implementing transit-oriented development (TOD). Of particular interest is the articulation of town planning policy through to implementation of development change on land around railway stations. A series of investigations include policy analysis and development mapping using Perth, Western Australia, as a case study. This research found that development change has been slow despite long policy lead times, and implementation has been inconsistent and patchy. Development planning for TOD has faltered, especially in relation to station precincts on new railways. Where development change has occurred, the greatest success has been through the use of public development agencies rather than through conventional planning approaches. Significant action in town planning is needed if development is to be delivered to a greater number of station precincts across the metropolitan area.